Association between admission hypoglycaemia and in-hospital and 3-year mortality in older patients with acute myocardial infarction. Issue 18 (28th July 2010) - Yang, Shi-Wei; Zhou, Yu-Jie; Hu, Da-Yi; Nie, Xiao-Min; Liu, Yu-Yang; Hua, Qi; Wang, Xian; Li, Hong-Wei; ,
Abstract : Objective: To assess the association between fasting plasma glucose (FPG) levels on admission and mortality in older patients with acute myocardial infarction (AMI), and compare the effects of FPG levels on outcomes in the context of contemporary treatments, including drug treatment, percutaneous coronary intervention and coronary artery bypass grafting. Methods: From April 2004 to October 2006, 1854 older (age ≥65 years) patients with AMI were enrolled in the Beijing Elderly Acute Myocardial Infarction Study (BEAMIS) consecutively. Patients were categorised into 4 groups: hypoglycaemia group (N=443, 23.9%), FPG≤5 mmol/l; euglycaemia group (N=812, 43.8%), FPG≥ 5.1 to≤7.0 mmol/l (5–7 mmol/l); mild hyperglycaemia group (N=308, 16.6%), FPG≥ 7.1 to≤9.0 mmol/l (7–9 mmol/l); and severe hyperglycaemia group (N=291, 15.7%), FPG≥9.1 mmol/l. The primary end point was in-hospital and 3-year all-cause mortality from the day of admission. Results: Compared with the euglycaemia group, hypoglycaemia or hyperglycaemia groups were all associated with higher in-hospital and 3-year all-cause mortality. There was a U-shaped relationship between admission FPG levels and short- and long-term all-cause mortality. This U-shaped relationship applied equally to subgroups in the context of contemporary treatments. Conclusions: In older patients with AMI, increased as well as decreased admission FPG levels could predict higher in-hospital and 3-year mortality. There was a striking U-shaped relationship between admission FPG levels and short- and long-term mortality. An initial admission FPG level ≥ 5.1 to≤7.0 mmol/l may be desirable because it was associated with better clinical outcomes.